(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In this article we can see observation of the developing digital economy and its impact to economy. Tourism is an information-rich field, in which the collection, transmission, analysis and storage of information play an important role in decision-making at all levels of the field. In this regard, the formation and development of the digital economy is of great importance for the exchange of products, work and services in online virtual markets. In this process, without the physical meeting of the buyer and the seller, the concept of time and space loses its value for them, in which the latest information and communication technologies are actively used